Calcium levels and metabolic disturbance in renal disease patients receiving hemodialysis: a cross sectional study highlighting its association in dialysis patients - Elahi, Wajeeha; Syed, Ameen Zubair; Jamil, Bilal; Arif, Madiha; Qamar, Nazia; Adil, Rahila; Anwar, Adnan (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this study was to determine the disturbances in Calcium and other mineral levels in patients on hemodialysis at Tabba Kidney Institute, Karachi, Sindh, Pakistan. Methods: A cross sectional observational study through convenient sampling technique was conducted from January 2017 to August 2017 at Tabba Kidney Institute, Karachi after obtaining ethical approval. 255 patients, all above 18 years of age and on hemodialysis were included in the study. Multi-organ failure patients on dialysis, other systemic diseased patients on hemodialysis were excluded. Demographic variables, mineral levels, symptoms and supplementations were recorded. SPSS version 20.0 was used for data analysis. Results: A total of 255 patients on hemodialysis were selected and divided into groups depending upon median years of hemodialysis below and above 5 years of hemodialysis. Median and IQR of calcium were 8.8 and 8.2-9.1 mg/dl for below 5 years, 8.6 and 8.1-9.1 mg/dl for above 5 years (P value=0.44). Median and IQR of phosphate were 4.9 and 3.9-5.7 mg/dl for below 5 years and 4.6 and 3.7-5.5 mg/dl for above 5 years (P value=0.21). Median and IQR of parathyroid hormone were 393 and 212-699 pg/ml for below 5 years and 329 and 128-657 pg/ml for above 5 years. (P value=0.13) Median and IQR of albumin were 4.0 and 3.6-4.2 mg/dl for below 5 years and 4.0 and 3.8-4.3 for above 5 years (P value=0.30). Total of 18 (10.9%) had para thyroidectomy. Conclusions: Present study showed that significant difference in mineral levels did not exist in patients on hemodialysis as regards to the duration of dialysis. However clinical features had a tendency to decrease as duration of dialysis increased to above 5 years. Para thyroidectomy and itching were two main significant findings in this study.